Organic fertilizations and fertigation with chicken boiled manure for organic crop - Hata, Fernando Teruhiko; de Paula, Maria Tereza; Moreira, Amanda A.; Ursi Ventura, Mauricio; de Lima, Romário Fortunato; de Freitas Fregonezi, Gustavo Adolfo; Martinez de Oliveira, André Luiz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
In order to achieve high profit in agricultural crops, it is necessary that fertilization of the soil is carried out properly, avoiding over fertilization, which contributes to the sustainable management of the soil. The objective of this study was to evaluate the effect of organic fertilization with bokashi, penergetic and boiled chicken manure doses on the production and nutrient content of berries, leaf chlorophyll index and soil microbial biomass in strawberry cultivation. The experiment was conducted in protected cultivation, evaluating productive variables (individual weight of berries and total production per plant), nutrients of the berry (nitrogen, phosphorus and potassium), soil (carbon of microbial biomass) and chlorophyll index in sheets. The treatments were strawberry without fertilization (control), penergetic (1.5 g.L-1), bokashi (50 g per plant) and doses of boiled manure via fertigation (2.5; 5; 7.5 and 10%, diluted in water) in a completely randomized design with five replications. Strawberry plants fertilized with bokashi showed significantly higher means of berry biomass, total berry production per plant, leaf chlorophyll and carbon values ​​of soil microbial biomass. Doses of 7.5 and 10% of boiled poultry manure provided berries production similar to bokashi and both were superior to the control. Higher levels of nitrogen, phosphorus and potassium were found with bokashi treatment and treatments with EF 7.5 and 10% obtained higher averages for phosphorus content in berries, only.